Hormone resistance and short stature: A journey through the pathways of hormone signaling. (1st October 2021) - Scalco, Renata C.; Correa, Fernanda A.; Dantas, Naiara C.B.; Vasques, Gabriela A.; Jorge, Alexander A.L.
Abstract: Hormone resistances have been described in association with growth disorders, the majority involving the growth hormone (GH)/insulin-like growth factor 1(IGF-1) axis or hormones with specific paracrine-autocrine actions in the growth plate. Defects in hormone receptors or in proteins involved in intracellular signal transduction (post-receptor defects) are the main mechanisms of hormone resistance leading to short stature. The characteristic phenotypes of each of these hormonal resistances are very distinct and bring with them important insights into the role of each hormone and its signaling pathway. In this review, we discuss the molecular and clinical aspects of the main hormone resistances associated with short stature in humans. Highlights: Hormone resistances can affect the human growth process. Defects in the receptors or in the signaling proteins lead to hormone resistance. The phenotypes of hormonal resistances are very distinct. The diverse phenotypes bring important insights into the role of each hormone.